The town that never sleeps : an illustrative guidebook of Ipoh old town - Wong, Yei Mun, (Universiti Malaysia Sarawak (UNIMAS), 2015)
Ipoh old town is a nostalgic town consists of the older and pre-war architectures such as the government buildings, shop houses, residences and historical landmarks. Other than that, the street art in Ipoh become the attraction of the public that brings the new tourists and boost up Malaysia tourism and economy sectors. However, most of the tourists could not find the exact location of the attractions because of the poor usage of illustration on the map and brochure which lack of the descriptions of the attractions from the Perak Tourist Information Centre. The main objective of this project is to come out with a illustrative guidebook to help the visitors in searching for attractions in old town. My inspiration to come out with this guidebook is to show the nostalgic feel of Ipoh old town through illustration which can attract the readers and also the illustration book lovers.